Dental care for patients with special needs: Challenges in the public health network (Research, Society and Development, 2023)
Objectives: Observing the challenges and importance of the Brazilian public health network, as well as the great demand for dental care for people with special needs, this review seeks to analyze the correlation between the two areas, seeking to understand the historical context from the trigger to the present day and understand the process of individuals' struggle to have equal access. Methodology: The present study is a literature review, to carry out the research scientific productions that are related and show coherence with the theme in its main aspects were included. Results: The authors report the difficulties faced by dental surgeons in oral health services, highlighting the limitations given to patients and the difficulties faced by caregivers in being able to adequately clean the oral cavity, requiring professional preparation with a more humanized and technique from its training to the provision of services, thus ensuring the right to inclusion of disabled people, so that there is a more effective result in treatment. Conclusion: Therefore, a greater investment of resources is necessary to better assist patients with disabilities (PwD), and professionals more prepared for the work environment.